2022
DOI: 10.1097/mog.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights on functional heartburn and reflux hypersensitivity

Abstract: Purpose of reviewRome IV experts have proposed that gastroesophageal reflux disease (GERD) should be diagnosed only in patients with abnormal esophageal acid exposure, and that reflux hypersensitivity (RH) and functional heartburn (FH) both should be considered functional conditions separate from GERD. Although past and recent evidence support that FH can be completely distinguished from GERD, the concept that RH is not GERD is highly questionable. This review attempts to provide current data on these issues.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…RH is defined by the presence of esophageal symptoms in response to reflux events despite normal total AET, with positive reflux‐symptom correlation using SI and/or SAP. Mechanistically, this can be explained by esophageal hypersensitivity, with lowered threshold for chemo‐ and mechanosensitivity, abnormal central processing of sensation, and hypervigilance 40–42 . However, Savarino et al found that the prevalence of dilated intracellular spaces in RH patients was increased similar to nonerosive reflux when compared to functional heartburn or healthy controls, indicating that some RH patients have characteristics within the GERD realm rather than a pure disorder of brain–gut interaction 43 .…”
Section: The Role Of Nonacid Reflux In Gerd Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…RH is defined by the presence of esophageal symptoms in response to reflux events despite normal total AET, with positive reflux‐symptom correlation using SI and/or SAP. Mechanistically, this can be explained by esophageal hypersensitivity, with lowered threshold for chemo‐ and mechanosensitivity, abnormal central processing of sensation, and hypervigilance 40–42 . However, Savarino et al found that the prevalence of dilated intracellular spaces in RH patients was increased similar to nonerosive reflux when compared to functional heartburn or healthy controls, indicating that some RH patients have characteristics within the GERD realm rather than a pure disorder of brain–gut interaction 43 .…”
Section: The Role Of Nonacid Reflux In Gerd Populationsmentioning
confidence: 99%
“…Mechanistically, this can be explained by esophageal hypersensitivity, with lowered threshold for chemo-and mechanosensitivity, abnormal central processing of sensation, and hypervigilance. [40][41][42] However, Savarino et al found that the prevalence of dilated intracellular spaces in RH patients was increased similar to nonerosive reflux when compared to functional heartburn or healthy controls, indicating that some RH patients have characteristics within the GERD realm rather than a pure disorder of brain-gut interaction. 43 This raises the likelihood of even WAR having epithelial access in activating chemosensitive receptors, thereby contributing to damage to esophageal mucosal integrity.…”
Section: Reflux Hypersensitivitymentioning
confidence: 99%
“…After the exclusion of eosinophilic esophagitis and major motility disorders, approximately 1/3 of such patients will be categorized as having reflux hypersensitivity (RH) or functional heartburn (FH) according to the existence or not of a correlation between symptoms and reflux episodes 2,3 . FH and RH are characterized by normal esophageal acid exposure, 4 although, patients with RH show a positive correlation of their symptoms to reflux episodes and may be benefited by proton pump inhibitor (PPI) therapy 5 . On the contrary, patents with FH have an increased rate of other Functional Gastrointestinal diseases 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…reflux episodes and may be benefited by proton pump inhibitor (PPI) therapy. 5 On the contrary, patents with FH have an increased rate of other Functional Gastrointestinal diseases. 6,7 Previous studies showed that, compared to patients with FH, patients with RH show higher rates of hiatus hernia (HH) existence, acid exposure time (AET), increased total number of refluxes (acid and nonacid) and refluxes with proximal extent.…”
mentioning
confidence: 99%
See 1 more Smart Citation